Urban sustainability in the context of maqasid al-shariah : a study on Malaysian Urban Indicators Network (MURNInet) - Nurul Aida binti Salim (Kulliyyah of Architecture and Environmental Design, Internationai Islamic University Malaysia, 2015)
The idea for sustainability in Malaysia had been incorporated in the nation's development plans since The Third Malaysia Plan (1976-1980) until the latest Tenth Malaysia Plan (2011-2015). To monitor the level of sustainability in particular urban area, the Federal Town and Country Planning Department initiated the MURNInet (Malaysian Urban Indicators Network) program in 2002. In 2005 the Guideline and Manual on MURNInet comprising 55 indicators within 11 sectors was launched to guide the 151 Local Authorities under the Ministry of Housing and Local Government to participate in this program. Thus, it is the aim of the research to study the incorporation of the sustainability concepts in the perspective of Islam into the present practices of urban sustainability in Malaysia. In so doing, Malaysian Urban Indicators Network (MURNInet) was studied within the context of Maqasid al-Shariah.In this regard, Imam al-Shatibi (d. 1388 CE) in his book; al-Muwafaqat explained Maqasid al-Shariah as the preservation of religion, life, intellect, lineage and wealth under the element of Daruriyyat(necessities) followed by Hajiyyat (needs) and Tahsiniyyat(luxuries). This research engages mixed-method research methodologies involving content analysis, questionnaire survey and Focus Group Discussion (FGD). Purposive sampling was adopted for this research consisting of Majlis Bandaraya Shah Alam, Majlis Perbandaran Bentong and Perbadanan Putrajaya as well as their respective State Town Planning Departments based on their achievement of sustainable cities status in 2008, 2009 and 2010 respectively. The research found that there was inappropriate basis/ foundation of the formulation of MURNInet due to lack of understanding on Maqasid al-Shariah consequently gave effect to the indicators itself. It is hoped that education and training on Maqasid al-Shariah, mutual consultation between Town Planner and Muslim jurists as well as full support and commitment from the relevant authority, theidea of Maqasid al-Shariah can be successfully embedded in present sustainability indicators towards achieving Islamic built environment.